Preparation and structural analysis of (±)-cis-ethyl 2-sulfanylidenedecahydro-1,6-naphthyridine-6-carboxylate and (±)-trans-ethyl 2-oxooctahydro-1H-pyrrolo[3,2-c]pyridine-5-carboxylate - Schwehm, Carolin; Lewis, William; Blake, Alexander J.; Kellam, Barrie; Stocks, Michael J. (International Union of Crystallography, 2014)
Bicycle ring closure on a mixture of (4aS,8aR)- and (4aR,8aS)-ethyl 2-oxodecahydro-1,6-naphthyridine-6-carboxylate, followed by conversion of the separated cis and trans isomers to the corresponding thioamide derivatives, gave (4aSR,8aRS)-ethyl 2-sulfanylidenedecahydro-1,6-naphthyridine-6-carboxylate, C11H18N2O2S. Structural analysis of this thioamide revealed a structure with two crystallographically independent conformers per asymmetric unit (Z′ = 2). The reciprocal bicycle ring closure on (3aRS,7aRS)-ethyl 2-oxooctahydro-1H-pyrrolo[3,2-c]pyridine-5-carboxyl-ate, C10H16N2O3, was also accomplished in good overall yield. Here the five-membered ring is disordered over two positions, so that both enantiomers are represented in the asymmetric unit. The compounds act as key intermediates towards the synthesis of potential new polycyclic medicinal chemical structures.